Profil Pembelajaran Fisika dalam Penerapan Kurikulum Merdeka dan P5 di Sekolah Menengah Atas - Febrian Virijai; Riandi Riandi; Diana Rochintaniawati; Eka Cahya Prima; Dadi Rusdiana; Resti Warliani; Diah Wahyuni; Mellyzar Mellyzar; Ridwan Ridwan; Adhara Jasid (Universitas Nurul Huda, 2024)
This study aims to analyze the implementation of physics learning in the context of the Independent Curriculum and the Pancasila Student Profile (P5) in one of the state senior high schools in Indragiri Hilir Regency, Riau Province. The Independent Curriculum is designed to provide greater freedom to schools and teachers in designing and implementing the learning process, with an emphasis on project-based learning and the development of student competencies as a whole. This requires case study research to see the obstacles in the implementation of KM and P5. This study uses a mixed methods, qualitative with interviews with physics teachers and analysis of learning device documents and quantitative with observation of questionnaires to 28 students. The results of the study indicate that the implementation of the Independent Curriculum in physics learning has been implemented, but there are obstacles in teacher readiness, difficulty in student understanding, and limited laboratory equipment and materials. In conclusion, the implementation of physics learning with the Independent Curriculum and P5 in Indonesia shows great potential in improving the quality of education and developing student skills and character. However, teacher readiness in implementation and infrastructure are needed to ensure the success of this implementation evenly across schools.